The PENCABUTAN KUASA SECARA SEPIHAK OLEH PEMBERI KUASA: PENCABUTAN KUASA - NI MADE, TRISNA DEWI (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The unilateral revocation of power of attorney by the grantor is a common practice in civil legal relationships, but it often raises legal issues when carried out without regard to the interests and legal position of the attorney. This article specifically discusses the legal basis for revocation of power of attorney based on Article 1813 of the Indonesian Civil Code (KUHPerdata), which grants the grantor the authority to revoke the power at any time, while also examining the limitations of that authority to protect the rights of the attorney. The focus of this study is directed at conditions where unilateral revocation may cause harm, create potential for breach of contract, and contradict the principle of good faith. The method used in this study is a normative-juridical approach based on statutory and doctrinal analysis. The findings indicate that although, normatively, power of attorney can be revoked freely, in practice there are both legal and moral limitations—especially when the power of attorney has been partially exercised, involves the interests of the attorney, or is revoked suddenly without valid reason. Under such conditions, revocation may give rise to liability for compensation to the attorney and be deemed contrary to the principles of justice and good faith. This article recommends the need for updating the norms of the Civil Code to provide procedural clarity concerning the revocation of power of attorney, including notification requirements, regulation of reasonable time limits, and compensation for resulting losses. It is expected that such reforms would create legal certainty and balanced protection for both the grantor and the attorney in the practice of power of attorney agreements.